The malleability of international entrepreneurial cognitions: a natural quasi-experimental study on voluntary and involuntary shocks. Issue 3 (11th January 2022) - Clark, Daniel R.; Pidduck, Robert J.; Tietz, Matthias A.
Abstract : Purpose: The authors investigate the durability of international entrepreneurial cognitions. Specifically, they examine how advanced business education and the Covid-19 pandemic influence international entrepreneurial orientation disposition (IEOD), and subsequently entrepreneurial intentions (EIs), to better understand the psychological dynamics underpinning the drivers of international entrepreneurship. Design/methodology/approach: Against the backdrop of emerging entrepreneurial cognition and international entrepreneurial orientation research, the authors theorize that both a planned business education intervention (voluntary) and an unforeseeable radical environmental (involuntary) change constitute cognitive shocks impacting the disposition and intention to engage in entrepreneurial efforts. The authors use pre- and post-Covid-19 panel data ( n = 233) and uniquely identify the idiosyncratic cognitive effects of Covid-19 through changes in the OCEAN personality assessment. Findings: Findings demonstrate that when individuals' perceived psychological impact of Covid-19 is low, business education increases IEOD. Conversely, the effects of a strongly perceived Covid-19 impact reduce the risk-taking and proactiveness components of the IEOD scale. The authors trace the same effects forward to EIs. Research limitations/implications: This paper contributes to a greater understanding of the resilience of entrepreneurial dispositions through an empirical test of the IEOD scale and shows its boundary conditions under planned intervention as well as unplanned externally induced shock. Practical implications: The study offers a first benchmark to practitioners of the malleability of international entrepreneurial dispositions and discusses the potential to encourage international entrepreneurial behaviour and the individual-level dispositional risk posed by exogenous shocks. Originality/value: The study uniquely employs a baseline measure of all our constructs pre-Covid-19 to discern and isolate the pandemic impact on entrepreneurial dispositions and intentions, responding to recent calls for more experimental designs in entrepreneurship research.